The Relationship between Listening to Murottal Al-Qur'an and Improving Adolescent Mental Health - Saiful Bahri; Andriyani Andriyani; Masyitoh Masyitoh; Iswan Iswan; Irna Hasanah (Indonesian Journal of Islam and Public Health, 2022)
According to WHO, health is a state where not only physically perfect but mentally and socially free from any disease or disability. WHO also explains that mental health in the world affects around 24 million people, and this is more common in adolescents around their 20s. Adolescent boys are the ones who tend to experience these mental health. Meanwhile, according to the Basic Health Research (Riskesdas) in 2018, it was stated that the population aged > 15 years experienced mental and emotional disorders as many as 19 million people and also experienced depression as many as 12 million people. The writing of this literature review was conducted to find out about the notion of mental health, whether there is a relationship between listening to the Murottal Al-Qur'an and improving health in adolescents, and to find out what the effects are after listening to the Murottal Al-Qur'an. The method used is analysis through several pieces of literature. 8 articles are used as references which are considered to represent the entire scientific article. The literature used is in the form of research journals or scientific articles with a span of 2017-2021. From several literature reviews, with various methods used by researchers, such as the pretest-posttest method, pre-experimental design, case studies, etc. It can be concluded that there is a relationship between listening to murottal Al-Qur'an and improving mental health in adolescents